Hubungan Pemberian Konseling KB Dengan Pemilihan Alat Kontrasepsi IUD - Herliana Herliana (LPPM Sikes Panca Bhakti Bandar Lampung, 2019)
Intra uterine device (IUD) is a contraceptive method that is used for a long time, so that it is effective in preventing pregnancy, the fact that the use of IUD contraceptive methods tends to decrease. The purpose of this study was to determine the relationship of family planning counseling with the selection of IUD contraception. This research is analytical using a case control design, for 200 respondents divided into 100 IUD acceptor sample groups and 100 control groups who did not use an IUD using Probability Statistick Random Sampling. Tool for collecting data using questionnaires, analyzing data with Chi-sqare tests. The results of the study concluded that more than half of the respondents were not given family planning counseling, namely 51 respondents (51%), some respondents used an IUD as many as 100 respondents and some respondents (50%). The conclusion of the study is that there is a relationship between family planning counseling and the selection of IUD contraceptives in family planning acceptors (p value = 0.031), an OR of 1.9 means that there is a chance 1.9 times greater chance for IUD contraception if counseled. Health workers are expected to continue to improve health services, provide counseling in determining the use of contraceptives, provide information to the public about the benefits and benefits.